Fire hotspots in Sierra Madre Oriental, San Luis Potosí: spatial patterns and related factors - Muñoz Robles, Carlos Alfonso; Santana Arias, Rogelio (Instituto de Ecología, A.C., 2018)
Wildland fires are a fundamental process that shape and maintain the structure of forest ecosystems, and are the result of several environmental and socio-economic factors that interact at the landscape scale to produce specific spatial distribution patterns. The aim of this study was to characterize fire-hotspots patterns and identify the main environmental and anthropogenic factors influencing their density in the Sierra Madre Oriental of San Luis Potosí in the period 2000-2012. The inhomogeneous Ripley´s K function was used to characterize monthly spatial patterns of fire hotspots (second order effects). To identify the main variables and thresholds that best explained the occurrence of fire-hotspots, regression trees were built using kernel density (first order effects) as a continuous response variable. Evidence of aggregated, regular and random patterns was obtained at different spatial scales. Monthly rainfall, diurnal temperature, land use/cover, elevation, distance to populated areas and distance to unpaved roads had a high influence in the occurrence of fire hotspots. Our results can contribute to a better understanding of wildland fire dynamics in the study area and can be used for studies related to forest fire danger and risk by applying the thresholds of the main explaining variables.